Fascial dehiscence after laparotomy: simple closures versus mesh reinforcement - Lizondo, Marcos F.; Otta, María C.; Acosta, Antonela R.; Posse, Juliana; Duhalde, Juan M.; Díaz, Rubén E.; Eskinazi, Diego G. (Revista Argentina de Cirugía, 2026)
Background: fascial dehiscence after laparotomy is a serious problem and its management with simple fascial closure has a high recurrence rate (re-dehiscence). Objective: The aim of this study was to evaluate whether the use of mesh during early closure of fascial dehiscence decreases dehiscence recurrence. Material and methods: We retrospectively analyzed a cohort of adult patients with fascial dehiscence after laparotomy who underwent early fascial closure. Patients were divided into two groups: simple fascial closure (control group), and mesh reinforcement (intervention group). The primary outcome was recurrence 30 days after surgery. Results: The population was made up of 32 patients, 24 in the control group and 8 in the intervention group, resulting in a 3:1 ratio. Mean age was 61.09 years and 59.38% were men. The absolute risk of recurrence in patients with simple closure (control group) was 62.5% ( 95% CI, 40.59-81.2) while none of the patients undergoing mesh reinforcement (intervention group) experienced recurrences, demonstrating a statistically significant difference (p = 0.003). Conclusion: The use of mesh for early closure of fascial dehiscence after laparotomy reduces its recurrence without major surgical site complications